Genetic deletion of α7 nicotinic acetylcholine receptors induces an age-dependent Alzheimer's disease-like pathology. (November 2021) - Tropea, Maria Rosaria; Li Puma, Domenica D.; Melone, Marcello; Gulisano, Walter; Arancio, Ottavio; Grassi, Claudio; Conti, Fiorenzo; Puzzo, Daniela
Highlights: α7nAChR deletion causes an impairment of hippocampal synaptic plasticity and memory in 12-month-old mice. α7 KO mice present an age-dependent increase of Amyloid Precursor Protein expression and Aβ levels. α7 KO mice at 12 months of age show tau pathology. α7 KO mice at 12 months of age show hippocampal neuronal loss and an increase of GFAP-positive astrocytes. Abstract: The accumulation of amyloid-beta peptide (Aβ) and the failure of cholinergic transmission are key players in Alzheimer's disease (AD). However, in the healthy brain, Aβ contributes to synaptic plasticity and memory acting through α7 subtype nicotinic acetylcholine receptors (α7nAChRs). Here, we hypothesized that the α7nAChR deletion blocks Aβ physiological function and promotes a compensatory increase in Aβ levels that, in turn, triggers an AD-like pathology. To validate this hypothesis, we studied the age-dependent phenotype of α7 knock out mice. We found that α7nAChR deletion caused an impairment of hippocampal synaptic plasticity and memory at 12 months of age, paralleled by an increase of Amyloid Precursor Protein expression and Aβ levels. This was accompanied by other classical AD features such as a hyperphosphorylation of tau at residues Ser 199, Ser 396, Thr 205, a decrease of GSK-3β at Ser 9, the presence of paired helical filaments and neurofibrillary tangles, neuronal loss and an increase of GFAP-positive astrocytes. Our findings suggest that α7nAChR malfunction might precede Aβ and tau pathology, offering a different perspective to interpret the failure of anti-Aβ therapies against AD and to find novel therapeutical approaches aimed at restoring α7nAChRs-mediated Aβ function at the synapse.